Understand Chilfree's Gender Justice Perspective on YouTube Social Media Netnography - Aminulloh; Muhammad Maghfurrohman; Teti Indrawati Purnamasari; Ihsan Azhari (al-Afkar, Journal For Islamic Studies, 2024)
Children are a gift, trust and decoration from Allah, the Almighty Creator, for parents, as well as pride in the world and hope in life after death. Even for this purpose, sometimes married couples use various methods to have a child. However, as time goes by, some people have the view that children are a burden. So they decided not to have children (childfree). This research is aimed at digging deeper into a person's motives for choosing childfree and to find out how the Indonesian people view the ideology of childfree, which will then be analyzed using a gender justice approach. This research is qualitative research using netnography methods. In this research, researchers will look for data regarding someone's motives for choosing to be childfree using YouTube social media. Data was obtained by following the YouTube channels kick Andy and Camel.